2007
DOI: 10.1021/bc060280t
|View full text |Cite
|
Sign up to set email alerts
|

Biotinylated Photocleavable Polyethylenimine:  Capture and Triggered Release of Nucleic Acids from Solid Supports

Abstract: A biotinylated photocleavable polyethylenimine (B-PC-PEI) was designed and synthesized for the capture and controlled release of nucleic acids from solid supports. B-PC-PEI was synthesized via a 3-step reaction process and verified by 1 H NMR and mass spectrometry. In aqueous solution, the o-nitrobenzyl group within B-PC-PEI was efficiently cleaved by 5 min of 365 nm light exposure from a distance of 20 cm (9 mW/cm 2 ). When coupled to streptavidin-coated beads, the PEI domain of Cy5-labeled B-PC-PEI was relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…1 H NMR spectra’s confirmed that both constructs had PEI, PEG and mannose present and the peaks strongly corresponded to previously reported values (Handwerger and Diamond, 2007; Sagara and Kim, 2002). The signal for mannose at 7 ppm was weak due to the relatively low proportion of mannose in the overall construct composition.…”
Section: Discussionsupporting
confidence: 88%
“…1 H NMR spectra’s confirmed that both constructs had PEI, PEG and mannose present and the peaks strongly corresponded to previously reported values (Handwerger and Diamond, 2007; Sagara and Kim, 2002). The signal for mannose at 7 ppm was weak due to the relatively low proportion of mannose in the overall construct composition.…”
Section: Discussionsupporting
confidence: 88%
“…[30] Specifically, this system provides robust polyplex stability against polyanion- or serum-mediated disassembly, along with light-mediated release of a significant fraction of siRNA following light exposure. Light-induced structural changes remove the hydrophobic and cationic moieties responsible for siRNA binding and elicit a charge reversal along the mPEG- b -P(APNBMA) 23.6 polymer backbone, which may account for the enhanced dissociation of the siRNA structures in this work as compared with other approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Cationic polymers with the labile chemical features are the potential candidates to controlled release of RNA or DNA at the locus of delivery and/or required time 3. The mechanisms of release, of varying degree of success, include reductively,4–6 hydrolytically7–11 and photolytically degradable chemical bonds12 as a response to changes in pH, ionic strength, temperature and also light. The release of DNA occurs as a result of either the release of positive charges from the vehicle or switching the positively charged moieties to electrically neutral ones.…”
Section: Introductionmentioning
confidence: 99%